Case Report: Crown Resorption in a Patient With Junctional Epidermolysis Bullosa and Amelogenesis Imperfecta With LAMB3 Gene Mutations - Urzúa, Blanca; Krämer, Susanne; Morales-Bozo, Irene; Camacho, Claudia; Yubero, María Joao; Palisson, Francis; Fuentes, Ignacia; Ortega-Pinto, Ana (Frontiers in Dental Medicine, 2021)
Background: Epidermolysis bullosa (EB) corresponds to a series of conditions characterized by extreme fragility of the skin and/or mucous membranes. Of the four main types of EB, junctional EB (JEB) is the most associated with alterations in the teeth. The purposes of this study were to determine the clinical, histopathological, and ultrastructural characteristics of teeth with amelogenesis imperfecta (AI) in a patient with JEB, and compare them with control teeth, and correlate the findings with the mutations present in the patient. Case Report: The study was conducted on a 10-year-old patient with JEB carrier of two recessive mutations in the LAMB3 gene and absence of the laminin-332 protein (LM-332), determined by immunofluorescence on a skin biopsy. The patient presents hypoplastic AI with very thin and yellow-brown colored enamel. Extraction of two permanent molars was performed due to pain and soft tissue covering the crown, resembling pulp polyp or hyperplastic gingiva. Light and scanning electron microscopy (SEM) revealed very thin enamel varying from complete absence to 60 μm, absence of normal prismatic structure, and presence of a cross-banding with a laminated appearance. The histopathological study revealed granulation tissue causing external crown resorption. Conclusion: Although coronary resorption has been reported in patients with syndromic and non-syndromic AI, this is the first clinicopathological report of coronary resorption in partially erupted teeth in patients with JEB with mutations in the LAMB3 gene and hypoplastic AI. In patients with this condition, the presence of partially erupted teeth with soft tissue covering part of the crown, without a periodontal pocket, and with a radiographic image of partial coronal radiolucency should lead to suspicion of external coronary resorption.